SIMULATION OF QUANTUM SEARCH ALGORITHM - Rina Refianti; Achmad Benny Mutiara (Faculty of Computer Science - Universitas Indonesia, 2013)
The rapid progress of computer science has been accompanied by a corresponding evolution of computation, from classical computation to quantum computation. As quantum computing is on its way to becoming an established discipline of computing science, much effort is being put into the development of new quantum algorithms. One of quantum algorithms is Grover's algorithm, which is used for searching an element in an unstructured list of N elements with quadratic speed-up over classical algorithms. In this work, Quantum Computer Language (QCL) is used to make a Grover's quantum search simulation in a classical computer document.